Wear Resistance of Ceramic Cutting Inserts Using Nitride Coatings and Microtexturing by Electrical Discharge Machining - Marina A. Volosova; Anna A. Okunkova; Elena Y. Kropotkina; Enver S. Mustafaev; Khasan I. Gkhashim (Eng)
Today, the machining of heat-resistant alloys based on triple, quad, or penta equilibria high-entropy alloy systems of elements (ternary, quaternary, quinary iron-, titanium-, or nickel-rich alloys), including dual-phase by Gibb’s phase rule, steels of the austenite class, and nickel- and titanium-based alloys, are highly relevant for the airspace and aviation industry, especially for the production of gas turbine engines. Cutting tools in contact with those alloys should withstand intensive mechanical and thermal loads (tense state of 1.38·108–1.54·108 N/m2, temperature up to 900–1200 °C). The most spread material for those tools is cutting ceramics based on oxides, nitrides of the transition and post-transition metals, and metalloids. This work considers the wear resistance of the cutting insert of silicon nitride with two unique development coatings — titanium–zirconium nitride coating (Ti,Zr)N and complex quad nitride coating with TiN content up to 70% (Ti,Al,Cr,Si)N with a thickness of 3.8–4.0 µm on which microtextures were produced by the assisted electric discharge machining with the electrode-tool of ø0.25 mm. The microtextures were three parallel microgrooves of R0.13+0.02 mm at a depth of 0.025−0.05. The operational life was increased by ~1.33 when the failure criterion in turning nickel alloy was 0.4 mm.